STRENGTHENING INTEGRATED ENVIRONMENTAL POLICIES THROUGH A GREEN AND CIRCULAR ECONOMY APPROACH TO ENCOURAGE MSME EMPOWERMENT AND POVERTY ALLEVIATION - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (CV. Radja Publika, 2026)
This study aims to analyze the influence of integrated environmental policies through a green and circular economy approach in encouraging MSME empowerment and poverty alleviation. The research approach used is mixed methods, namely a combination of quantitative and qualitative methods. Quantitative data were analyzed using Partial Least Squares (PLS-SEM), while qualitative data were obtained through in-depth interviews and field observations. The results of the quantitative study indicate that integrated environmental policies have a significant effect on the green and circular economy, with a T-statistic of 4.663 and P-values ​​of 0.000. The green and circular economy also has a significant effect on MSME empowerment and poverty alleviation with a T-statistic of 4.762 and P-values ​​of 0.000. In addition, integrated environmental policies also have a direct effect on MSME empowerment and poverty alleviation, and are proven to have an indirect effect through the mediating variable of the green and circular economy. The research model shows an R-square value of 0.677 for the green and circular economy variable and 0.848 for the MSME empowerment and poverty alleviation variable, which indicates a strong explanatory power of the model. Qualitative results indicate that the implementation of a green and circular economy in MSMEs is still in the transition phase, with positive impacts in the form of business efficiency, increased revenue, and expanded market access. However, obstacles remain, including limited capital, low environmental literacy, and limited access to technology. Nevertheless, significant opportunities exist through government policy support, green financing, and MSME digitalization.